Investment Decision Making: The System Performance of the Portfolio of Shares on Index Business 27 (2017-2018) using the Model of Constant Correlation - Nugroho, Mulyanto; Nurcahyo, Yusuf Eko (International Review of Management and Marketing, 2019)
Share Capital Market industry now is growing rapidly and significant value of their transactions reach hundreds of trillion rupiah with the risk can virtually so small that this is an opportunity to invest. But although have a small risk in investing needed a strategy or the right method to reduce a risk that will happen. One model that will be used to know the system performance of the portfolio is to use the model of constant correlation on business index 27th. This research is done with the period of 2 years i.e. early 2017 until the end of the year 2018 with stock data into Business index 27th. From the period of the research during 2 this year in the index heading 27th selected all shares are numbered 27 share. The results from the model of constant correlation on 27th Business Index is as follows: BBCA (44.76%), AKRA (35,91%), PTBA (12,10%) and BDMN (7,23%). Portfolio Return (ERP) 27th Business Index of 0.079917153, Portfolios Risk (Ïƒp) Bisnsis 27th of 0.03149347. The results of the measurement of the performance of the portfolio using Sharpe index of 0.123296087, 0.007067026 Treynor Index of index and Jansen of 0.0069643. The results of the analysis show that the performance of the portfolio of shares of Business Index 27th better, but the level of portfolio volatility index shares Busines 27th vulnerable to changes in the market. Keywords: Information system, Stock portfolio performance, Decession support system JEL Classifications: M4, M40 DOI: https://doi.org/10.32479/irmm.8091